Triterpenoids From Swietenia mahagoni L Jacq. and Their Cytotoxic Activity against MCF-7 Breast Cancer and CV-1 Normal Kidney Cell Lines - Supratman, Unang; Abdullah, Fajar Fauzi; Farabi, Kindi; Nurlelasari, Nurlelasari; Awang, Khalijah; Nafiah, Mohamad Azlan (Universitas Jenderal Soedirman, 2024)
ABSTRACT. Triterpenoid is a group of natural products with various remarkable activities, including cytotoxic. One of the sources for this type of compounds is Swietenia genus belong to Meliaceae family. This genus known to contains various secondary metabolites including limonoids, flavonoids, and triterpenoids. Especially for triterpenoid, there is limited report on isolation as well as biological activity from Swietenia genus, such as Swietenia mahagoni. In this research, three triterpenoid compounds have been successively isolated and identified from n-hexane extract, namely, (-)-leucophyllone (1), toonaciliatavarin E (2), and moronic acid (3). All isolated were assed against MCF-7 breast cancer and CV-1 normal kidney cell lines. The result showed that only moronic acid (3) performed moderate activity against two cells with IC50 of 63.10 and 48.04 µM, respectively. The other isolated compounds (1 and 2) showed weak cytotoxicity with IC50 > 500 µM. Based on preliminary structure activity relationship, revealed that pentacyclic triterpenoid (moronic acid, 3) showed stronger cytotoxicity compare with tetracyclic triterpenoids (-)-leucophyllone (1) and toonaciliatavarin E (2). Keyword: Cytotoxicity, MCF-7 and CV-1, Switennia mahagoni, Triterpenoids.